Extended application of test results on durability of self-closing for doorsets and openable windows. Durability of self-closing of fire resistance and/or smoke control hinged and pivoted metal framed glazed doorsets and openable windows Part 4, (28th May 2021) - British Standards Institution,
No abstract available